Understanding the Multiple Role of Mitochondria in Parkinson’s Disease and Related Disorders: Lesson From Genetics and Protein–Interaction Network - Nicoletti, Valentina; Palermo, Giovanni; Del Prete, Eleonora; Mancuso, Michelangelo; Ceravolo, Roberto (Frontiers in Cell and Developmental Biology, 2021)
As neurons are highly energy-demanding cell, increasing evidence suggests that mitochondria play a large role in several age-related neurodegenerative diseases. Synaptic damage and mythochondrial dysfunction have been associated with early events in the pathogenesis of major neurodegenerative diseases, including Parkinson’s disease, atypical parkinsonisms and Huntington disease. Disruption of mitochondrial structure and dynamic is linked to increased levels of reactive oxygen species production, abnormal intracellular calcium levels and reduced mitochondrial ATP production. However, recent research has uncovered a much more complex involvement of mitochondria in such disorders than has previously been appreciated and a remarkable number of genes and proteins that contribute to the neurodegeneration cascade interact with mitochondria or affect mitochondrial function. In this review we aim to summarize and discuss the deep interconnections between mitochondrial dysfunction and basal ganglia disorders, with an emphasis into the molecular triggers to the disease process. Understanding the regulation of mitochondrial pathways may be beneficial in finding pharmacological or non-pharmacological interventions to delay the onset of neurodegenerative diseases.